2017
DOI: 10.1038/s41598-017-11248-3
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-196b inhibits late apoptosis of pancreatic cancer cells by targeting CADM1

Abstract: Pancreatic cancer (PC), as the leading cause of cancer death worldwide, is one of the deadliest tumors with a very low 5-year survival rate. Therefore, it is urgent to seek new biomarkers of PC for more accurate and reliable treatments. To identify the differentially expressed miRNAs (DEM) in PC tissues, we performed the systematic microarray and qRT-PCR analyses. We found miR-196b was the top dysregulated DEM in PC tissues as compared with the corresponding adjacent tissues, and positively correlated with poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Moreover, our findings also exhibited a close relation between miR-196b expression and the pathological characteristics and prognosis of LSCC patients. Similar in pancreatic cancer, miR-196b was also positively associated with poor differentiation, tumor size, lymphatic invasion and TNM staging [37], and a high expression of miR-196b predicted a lower overall survival rate than those with a low expression in pediatric acute myeloid leukemia [11], further highlighting the promoting role of miR-196b in LSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our findings also exhibited a close relation between miR-196b expression and the pathological characteristics and prognosis of LSCC patients. Similar in pancreatic cancer, miR-196b was also positively associated with poor differentiation, tumor size, lymphatic invasion and TNM staging [37], and a high expression of miR-196b predicted a lower overall survival rate than those with a low expression in pediatric acute myeloid leukemia [11], further highlighting the promoting role of miR-196b in LSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Catuogno et al (28) showed that miR-34c protected lung cancer cells from paclitaxel-induced apoptosis. Wang et al (29) reported that miR-196b inhibited late apoptosis in pancreatic cancer cells. Cao et al (30) reported that overexpression of miR-196b enhanced viability and inhibited apoptosis of human HeLa and 293T cells.…”
Section: Role Of Lncrna Loc105374325 In Podocytes Of Fsgsmentioning
confidence: 99%
“…This is not the first time that miRNA has selectively affected the late-stage apoptosis of cancer cells. A previous study by Wang et al demonstrated that miRNA-196b promoted pancreatic cancer cell growth by inhibiting late apoptosis via negative regulation of CADM1 expression (66). Further studies are required to investigate the molecular mechanism of how miR-182 mediates late apoptosis in GIST cells.…”
Section: Discussionmentioning
confidence: 97%